Pengembangan Kurikulum Operasional Sekolah Berbasis Konteksual - Norma Sulistiyani; Rusmayadi Rusmayadi; Herlina Herlina; Muhammad Yusri Bachtiar; Salma Samputri (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
This study aims to develop a contextual-based operational school curriculum for early childhood education at PAUD TPQ Kreatif, Gowa Regency. The research employed a Research and Development method using the 4-D model (Define, Design, Develop, Disseminate). Data were collected through observation, interviews, questionnaires, and documentation. Data analysis included qualitative and quantitative methods, specifically assessing the validity, practicality, and effectiveness of the curriculum product. The findings indicate a strong need for a contextual-based curriculum to enhance the relevance of learning to students' daily lives. The developed curriculum comprises needs analysis, instrument preparation, and an implementation guidebook. The practicality of the curriculum, as rated by teachers, reached 85.93% (very practical), while its effectiveness was 91.40% (very effective), demonstrating the curriculum’s capability to achieve learning objectives optimally. The developed contextual operational school curriculum is suitable for use in early childhood education institutions and significantly contributes to improving the quality of meaningful and relevant learning.